The Transculturation of Brazilian Literary Criticism - Pellizzari, Thamiris Yuri Silveira (Opiniães, 2020)
In this article, it is intended to ponder over issues that concern the immanence between literary criticism and society, in the Brazilian context, taking into consideration Brazil’s dependence on European countries. For this purpose, it is reflected, in general, about the critical ideas from Eneida Maria de Souza, in her book Crítica cult (2002) that addresses Brazilian critical speech, as well as the great critic Antonio Candido, in particular, based on some parts of his book Formação da literatura brasileira (1959). It is intended to discuss the transculturation of Brazilian literary criticism, thinking about some relevant issues, like dependence, tradition, and the tireless search for the constructions of Brazilian literature that wants to be original.